Pengaruh Biaya Produksi dan Harga Jual terhadap Pendapatan Petani Jagung di Desa Ilomata Kecamatan Atinggola Kabupaten Gorontalo Utara - Anjelita Pajiri; Radia Hafid; Ardiansyah, Ardiansyah; Roy Hasiru; Fatmawaty Damiti (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to investigate whether production costs and selling price influence the income of corn farmers in Ilomata Vilage, Atinggola Sub-District, Gorontalo Utara Regency. Employing using a linier regression. The findings indicate a positive in Ilomata Village, Atingggola Sub-disctrict, Gorontalo Utara Regerency. The findings further confirm that production sosts and selling price exert a statistically significant influence on the income of these corn farmers in Ilomata Village, Atinggola Sub-district, Gorontalo Utara Regerency. Additionally, these findings demonstrate the value of coefficient of correlation (R) which further confirms that contribution of variable of production costs and selling price, simultaneously, elucitade corn farmers’ income 0.415 or 41.5%.